To determine lumbar lordosis and thoracic kyphosis in thoraco lumbo pelvic alignment in chronic low back pain patients in Central Indian Population - Bangeet Kaur, Dr. Pawan Kumar Mahato (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Alterations in sagittal thoraco-lumbopelvic alignment are frequently linked tochronic low back pain (CLBP), a common disorder that greatly affects quality of life. The purposeof this research is to examine lumbar lordosis and thoracic kyphosis, two measures of thoraco lumbopelvic alignment, in people living in Central India